Sleep quality responses to atmospheric variation: case studies of two elite female cyclists - Kinsman, T. A.; Hahn, A. A. G.; Gore, C. J.; Martin, D. (Journal of Science and Medicine in Sport, 2003)
Strategies applied during sleep to potentially enhance athlete performance use different atmospheric conditions. High altitude conditions are known to affect sleep adversely but the effects of mild-moderate altitude and O2 enrichment at mild altitude are uncertain. We performed case studies using two elite female road cyclists (mass and maximal aerobic power of 62 kg, 65.8 ml x kg(-1) x min(-1); 57 kg, 62.7 ml x kg(-1) x min(-1)) to examine changes in sleep for different atmospheric conditions applied throughout the preparation for, and during, an International Stage race. Conditions were: i) normoxia (600 m), ii) simulated moderate altitude (2650 m), iii) natural mild altitude (1380 m) and iv) O2 enrichment at mild altitude (30% O2@ 1300-1500 m). We measured respiratory disturbances, arousals, number of awakenings, blood oxygen saturation (SpO2), heart rate (HR), rapid eye movement sleep (REM) and deep sleep. Respiratory disturbances, SpO2 and HR responses were similar for both cyclists for all conditions. Compared with normoxia, both cyclists had somewhat reduced REM at natural mild altitude and moderate simulated altitude but differed in their REM and deep sleep responses to O2 enrichment. Compared with mild altitude, both showed increased awakenings and deep sleep with O2 enrichment. Only one cyclist clearly increased her REM sleep with O2 enrichment compared to mild altitude. Our data highlight two different sleep quality responses to atmospheric variation.